COVID-19 Vaccination: To Lead by Example or an Opportunity Lost. (December 2021) - Wolff, M.S.; Glick, M.
Coronavirus disease 2019 (COVID-19) has created a global health emergency. Vaccine hesitancy and tremendous misinformation about the actual science are leaving the public with significant confusion. However, sound epidemiologic science is guiding us to a clear path toward mitigating this modern-day scourge. It is remarkable how putting an end to current COVID-19 outbreaks has such a simple solution—convincing the public to accept getting vaccinated. The dental research, dental education, and dental practice communities have a unique opportunity to act as trusted public exemplars as well as trusted interpreters of the science for the public.